PENGATURAN HUKUM FINANCIAL TECHNOLOGY DI INDONESIA - Henri Christian Pattinaja (Jurnal Hukum dan Bisnis (Selisik), 2021)
Along with the progress of the era, technology and information systems developed in the community, this made it easier for humans in their daily activities. Looking at trends of shifting transactions, the world is shifting towards a new direction, that is, no longer using physical money, but using Financial Technology. The problem that is formulated is How is the history of the development of financial technology in Indonesia and How are the forms of legal protection arrangements for consumers who use financial technology in Indonesia. This study concludes that the evolution of FinTech that has been seen lately actually originated from credit card innovations in the 1960s, debit cards and terminals that provided cash, such as automated teller machines, ATMs in the 1970s. Then the credit card era was followed by the emergence of telephone banking in the 1980s and various financial products following the deregulation of capital markets and bonds in the 1990s. Furthermore, internet banking emerged, which then encouraged branchless banking and long-distance banking activities. Furthermore, mobile technology emerged which made it easier for financial transactions. And finally the electronic wallet technology was raised, with two companies known in Indonesia as Go-Pay and OVO. The legal protection itself is realized in the Law of the Republic of Indonesia Number 7 of 2014 concerning Trade, Law No.19 of 2016 concerning Amendment to Law Number 11 Year 2008 concerning Information and Electronic Transactions, Law of the Republic of Indonesia No.8 Year 1999 concerning Consumer Protection, as well as Law of the Republic of Indonesia Number 7 of 2011 concerning Currency. The latest additional regulatory protection from Bank Indonesia itself is by issuing Bank Indonesia Regulation No.19 / 12 / PBI / 2017 concerning the Implementation of Financial Technology